Sustainable intensification of water guzzling crops: Identifying suitable cropping districts of India - CHAND, PREM; RAO, SULAKSHANA; AGARWAL, PRIYANKA; JAIN, RAJNI (The Indian Journal of Agricultural Sciences, 2021)
With food sufficiency being achieved, emphasis of policy makers is now on to sustainable intensification in line with the objectives of Sustainable Development Goals (SDGs). Widening discrepancy between the water-resource supply and demand necessitates relook into the cropping pattern of the country. Based on district-level secondary data of area, productivity and level of groundwater extraction, this study aims to identify critical and potential area for cultivation of three major water-intensive crops, i.e. rice, wheat and sugarcane. Study found that 1.93 million ha of area under rice, mainly in north-western and western India, need a gradual shift. Nearly 43% of the rice cultivated area in eastern and north-eastern states of West Bengal, Odisha, Chhattisgarh and Assam has potential for further intensification of rice cultivation. In case of wheat, around 0.65 million ha of area, mostly in Rajasthan, is critical in terms of sustainability. Livestock is an integral part of agriculture in this region and hence diversification of wheat would require mixed strategy of shifting to alternative dual-purpose crops and wheat cultivation with water conservation technologies. Study further found that around 13543 ha of sugarcane in mainly in western Uttar Pradesh and Tamil Nadu is deterring the groundwater resources. Recommendations emanating from the study include differentiates agricultural price policy, payment for ecosystem services and greater focus on productivity enhancement in eastern India.